Let's get crackin' - Wong, Gwendolyn Jeng Teng (Nanyang Technological University, 2023)
‘Get cracking’ means to get started with something quickly. With Singapore’s fast-paced lifestyle, we often forget to fully immerse ourselves in the moment, thus overlooking the little joys in life. Even the act of eating might become a mindless activity, where people rush to finish their meals to continue on with their bustling lives, without savouring the food they are consuming. In Singapore, with the advent of convenience foods or processed foods, and the growing prioritisation of careers and academics in families, there is a decline of home cooking, and children have fewer opportunities to be involved in cooking and planning their meals. Cooking becomes a chore and a hindrance, and people increasingly turn to eating out or taking away food.